Secondary Dual-Language Learners and Emerging Pedagogies: The Intersectionality of Language, Culture, and Community. Issue 2 (3rd April 2019) - Ramirez, Pablo; Ross, Lydia
Abstract : We draw from an ethnographic research perspective to examine the potential benefits and pitfalls of dual-language secondary classrooms. The data collected come from multiple sources including classroom observations and teacher interviews from dual-language secondary classrooms. A secondary dual-language education conceptual framework is presented. Three dimensions of the DLE framework inform teachers' pedagogical practices in the classroom: bilingualism, culture, and community engagement. Further, in this article, recommendations for effective dual-language secondary classrooms are offered as a way to advance teachers' pedagogical practices that leverage students' language repertoire.